METHODS OF DEVELOPING CREATIVITY IN STUDENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the pedagogical approaches and effective methods for developing creativity in students. Creativity is one of the essential skills in modern education, shaping students’ problem-solving abilities, imagination, and innovation. The study highlights various psychological and pedagogical perspectives on creativity, emphasizing the role of teachers in fostering a creative learning environment. The article also presents the views of Uzbek and international scholars on the development of creative potential in the learning process.